Community Service Through the Implementation of Islamic Education in Arahan Kidul Village - Inka Dinda Thiara Qurrotunnisa; Didik Himmawan (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
The development of Islamic education in Indonesia is marked by the emergence of modern Madrasahs as a whole. This was motivated by parents' anxiety due to the lack of appropriate religious instruction for children in formal schools. So to date, the Madrasah Diniyah Educational Institution is still surviving, even though it still receives little attention from the government, both in terms of budget and personnel. Through the thematic KKN team, the service team carries out service in the Indramayu kidul direction. Before implementing the KKN, the service team of KKN participants conducted field observations to see what potential had to be developed and what things the service team of KKN participants had to do in the future. The potential that we can develop is also explored through interviews with the RW Chair, Residents, IRMA and MDTA Chair. Next, we conducted a survey in several places to find out which places we could use as a place to implement the work program that we had prepared. Next, we immediately implemented the work program that we had planned which included: Teaching the Koran for Madrasah children), Mothers' Recitation in the Mosque, Fathers' Recitation in the Mosque, Children's Maghrib Recitation (Tahfidz Guidance) in the Mosque, JUMSIH Activities ( Clean Friday) at the Mosque. This KKN service method uses a qualitative method. After implementing this KKN, the community, especially IRMA, was helped because of the lack of lecturers in the South direction and the lack of Human Resources for JUMSIH activities, and other results obtained were many children who were more fluent in reading Iqro and Al-Quran.